Characterization of enamel developmental defects in patients with orofacial clefts and their relationship to surgical procedures - Farias, Aline [UNESP]; Rojas-Gualdrón, Diego Fernando; Restrepo, Manuel; Zecchin, Karina Gottardello; Bussaneli, Diego Girotto [UNESP]; Yupanqui, Kasandra [UNESP]; Raposo-Amaral, Cassio Eduardo; dos Santos-Pinto, Lourdes [UNESP] (Springer Nature, 2023)
Aims: This study aimed to characterize the prevalence of development defects of enamel (DDE) in patients with cleft based on the cleft phenotype and explore the relationship between surgical procedures and different types of DDE. Material and methods: In this cross-sectional study, 290 standardized orthodontic documentation and medical records from a reference hospital were evaluated, which treated patients with: cleft lip (CL), cleft lip with alveolar bone involvement (CLa), cleft lip and palate (CLP), cleft palate (CP), cleft median (CM), and considering laterality as unilateral or bilateral. DDE was assessed using the Ghanim Index (2015). Information on surgical intervention periods was obtained from medical records. Statistical analyses were performed using prevalence ratio (PR) for DDE comparisons between cleft phenotypes and surgical procedures. Results: The prevalence of DDE was 77.2%. Demarcated hypomineralization was associated with CP and CLP, while hypoplasia was associated with CLa, especially when bilateral. Hypoplasia was also associated with the labial adhesion surgery. Conclusion: Demarcated hypomineralization was the most common DDE in this population, and the cleft phenotype influenced the type of DDE manifested. The lip adhesion surgery increased the chances of hypoplasia manifestation. Clinical relevance: The type of DDE in patients with cleft depends on the cleft phenotype. Understanding this susceptibility enables the multidisciplinary team to monitor dental development, thus allowing early diagnosis and timely referral to the pediatric dentist and better prognoses.
Keywords: Cleft lip; Cleft lip and palate; Cleft palate; Dental enamel hypomineralization; Dental enamel hypoplasia